2005
DOI: 10.1007/s00170-003-2039-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of heat fluxes during high-speed drilling

Abstract: Heat fluxes on each cutting edge of a carbide double cutting drill are estimated during a high-speed machining process from temperature measurements in the drill tool and a direct model that has been established using the non integer system identification approach. A single experiment is required in order to characterize the transient thermal behavior of the tool. The non integer system identification method is based on the recursive linear least square algorithm. The inverse method is based on the constant fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Devries et al embedded iron-constantan thermocouples at different points on the flank face of the tool to measure the drilling temperature, and they also found that the workpiece properties, such as the presence of pilot holes and the size, affected the drilling temperature substantially [35]. Battaglia et al inserted the thermocouple into the oil hole of a carbide double cutting drill to determine temperature distribution and estimated the heat fluxes on the cutting edge [36]. Li et al embedded thermocouple into carved groove on a fixed drill that was continuously sprayed with coolant to determine its temperature distribution when drilling a rotating titanium workpiece.…”
Section: Embedded Thermocouplementioning
confidence: 99%
See 1 more Smart Citation
“…Devries et al embedded iron-constantan thermocouples at different points on the flank face of the tool to measure the drilling temperature, and they also found that the workpiece properties, such as the presence of pilot holes and the size, affected the drilling temperature substantially [35]. Battaglia et al inserted the thermocouple into the oil hole of a carbide double cutting drill to determine temperature distribution and estimated the heat fluxes on the cutting edge [36]. Li et al embedded thermocouple into carved groove on a fixed drill that was continuously sprayed with coolant to determine its temperature distribution when drilling a rotating titanium workpiece.…”
Section: Embedded Thermocouplementioning
confidence: 99%
“…Sorrentino [34] Battaglia [36] Li [37] DeVries [35] Weinert [33] Cardoso [40] Bağci [32] Bono [42] Bono [41] Drill-foil Thermocouple Bhowmick[52] TASKESEN [53] Ueda [43] Yang [44] Pérez [39] Dörr [56] Usama A [57] Reissig [25] Mills [26] Wright [27] Okada [46] Oezkaya [55] Beno [47] obtain drilling temperature remotely. There are many non-contact measurement methods, but the methods used in drilling are completely limited to infrared radiation.…”
Section: Tool-work Thermocouplementioning
confidence: 99%
“…The mathematical representation of parameter estimation problem is as follows (Eq. 11): subject to (11) In fact, this is a one-dimensional optimization problem, which can be iteratively solved, for instance, by the golden section method [35]. As can be seen in Fig.…”
Section: Two-stage Procedures For Hypotheses Verification 361 Firstmentioning
confidence: 99%
“…To avoid a non-linear heat conduction problem related to the temperature-dependent properties of materials, a model expressed in a recursive transfer function form was proposed. Lately, this approach has been extended to drilling and milling [11,12]. In all cases, retrieved heat flux values were used for estimation of cutting tool temperature.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the heat distribution, researchers have studied heat fluxes into the tool, chip and workpiece. A number of papers have been devoted to heat flux determination in different machining processes such as deep grinding [5], high-speed drilling [7], dry machining of aeronautic aluminum alloy [9], MQL tapping and reaming [10] or devoted to prediction of heat flux distribution [6] and its effect on tool thermal deformation [8]. On the one hand, heat flux is the boundary condition (initial data) for the heat transfer equation, and on the other hand, it is a parameter that is almost impossible to measure due to the small area of the tool-chip contact and the aggressiveness of the cutting process.…”
Section: Introductionmentioning
confidence: 99%